Electrical properties of materials - Solymar, L. (Oxford University Press, 2010)
This work offers a simple treatment of the relevant mathematics and a clear guide to applications for students in electrical and electronic engineering. The fundamental ideas relevant to the understanding of the electrical properties of materials are emphasized.